2011
DOI: 10.5120/2183-2754
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Detection and Classification of Plant Diseases

Abstract: We propose and experimentally evaluate a software solution for automatic detection and classification of plant leaf diseases. The proposed solution is an improvement to the solution proposed in [1] as it provides faster and more accurate solution. The developed processing scheme consists of four main phases as in [1]. The following two steps are added successively after the segmentation phase. In the first step we identify the mostlygreen colored pixels. Next, these pixels are masked based on specific threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
184
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(215 citation statements)
references
References 13 publications
(20 reference statements)
0
184
0
1
Order By: Relevance
“…K-Means clustering and neural network have been formulated for clustering and classification of diseases that affect on plant leaf. They found that proposed approach, which can significantly support an accurate detection of leaf diseases in little computational effort [13].…”
Section: Literature Surveymentioning
confidence: 99%
“…K-Means clustering and neural network have been formulated for clustering and classification of diseases that affect on plant leaf. They found that proposed approach, which can significantly support an accurate detection of leaf diseases in little computational effort [13].…”
Section: Literature Surveymentioning
confidence: 99%
“…Neural Network is popular method in pattern recognition case and its performance in pattern recognition has been proven. Some research about pattern recognition used Neural Network [11][12][13][14][15][16][17][18]. The machine learning process with neural network is depicted in Fig.…”
Section: Neural Networkmentioning
confidence: 99%
“…Generally the disease detection activities are performed by specialists by visually inspecting each sample, which is a very tedious and time consuming task. Hence automatic machine vision technology has acquired a significant role in this field [3].…”
Section: Introductionmentioning
confidence: 99%